2016
DOI: 10.1163/1937240x-00002453
|View full text |Cite
|
Sign up to set email alerts
|

The response of the wash-zone amphipod, Urohaustorius sp. (Amphipoda: Talitridae), to light, gravity, slope, and magnetic fields

Abstract: A B S T R A C TLittoral talitrid amphipods that traverse the intertidal zone have been the subject of many behavioural tests. These tests have emphasised the orientation cues required for the maintenance of these talitrids along specific zones on the land-sea axis (y-axis) of the littoral zone. Comparatively, little is known of the orientation cues required by amphipods living along the wash zone of beaches. Urohaustorius sp., family Urohaustoriidae (U. gunni Barnard and Drummond, 1982, but material unavailabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Ugolini et al (1998) stated that the solar compass in intertidal arthropods is used to assume an ecologically efficient escape direction. In experiments with Urohaustorius sp., a strong negative phototaxis overrode any magnetotactic response, even though gravity was determined to be the strongest orientation cue, testing in a compensated magnetic field produced no geotactic response when the amphipods were not given a direction for light (Rothsey and Andrew, 2016). Based on the results of the current study, this could also be the case for Notorchestia sp., as these amphipods appear to use a solar compass for y-axis orientation if too wet or too dry.…”
Section: Solar Compass Testingmentioning
confidence: 53%
See 2 more Smart Citations
“…Ugolini et al (1998) stated that the solar compass in intertidal arthropods is used to assume an ecologically efficient escape direction. In experiments with Urohaustorius sp., a strong negative phototaxis overrode any magnetotactic response, even though gravity was determined to be the strongest orientation cue, testing in a compensated magnetic field produced no geotactic response when the amphipods were not given a direction for light (Rothsey and Andrew, 2016). Based on the results of the current study, this could also be the case for Notorchestia sp., as these amphipods appear to use a solar compass for y-axis orientation if too wet or too dry.…”
Section: Solar Compass Testingmentioning
confidence: 53%
“…is capable of y-axis (landsea) orientation in a fashion similar to the intertidal talitrids Talitrus saltator (Arendse, 1978;Ugolini et al, 1991), Cryptorchestia corniculata (Craig, 1973a, b), Talorchestia martensii (Ugolini and Pardi, 1992), Atlantorchestoidea brasiliensis (Dana, 1853) (Cardoso, 2002), and Urohaustorius sp. (Rothsey and Andrew, 2016). In this study, orientation was shown to be influenced by either dehydration, whereby the amphipods oriented seawards, or inundation with seawater, where landward orientation prevailed.…”
Section: Solar Compass Testingmentioning
confidence: 62%
See 1 more Smart Citation